(untitled) (Stavební obzor - Civil Engineering Journal, 2019)
In regard to optimize the supporting plan of deep foundation pit, this paper used the unascertained measurement (UM) and data envelopment analysis (DEA) to conduct. In order to determine the relationship between influencing factors and the best bid plan, an evaluation model for deep foundation pit support schemes based on UM was developed. First, the information entropy (IE) was introduced to determine the weight of discriminant indices which consider the confidence identification criteria as the judgment principle of evaluation. Then, the optimal solution from all feasible support schemes was investigated. Finally, Fuzzy comprehension assessment- data envelopment analysis (FCA-DEA) was utilized to analyse the effectiveness of design plans, which was evaluated by UME subsequently. Applicability of the proposed UM-DEA model was tested with four real design cases of foundation projects. Results compared with other methods have shown the developed model is useful for concept design and decision making of supporting plan for deep foundation.